Comprometimento Organizacional dos Servidores Técnico-Administrativos do Centro de Tecnologia da UFC - Pereira, Lucivaldo de Sousa (2013)
The present study has as its central approach organizational commitment. A survey of quantitative trait was performed and scored as a theoretical basis concepts related to organizational commitment. Organizational commitment refers to how each person perceives the motivation of his relationship with the organization, which can be affective nature, reflecting a wish, instrumental, reflecting a need or normative, reflecting a must. Presented significant concepts of the topic and its importance for modern organizations. The main objective was to characterize the degree of organizational commitment of technical and administrative staff of the UFC CT, using the model conceptualization of the three components of organizational commitment, affective, instrumental and normative proposed by Meyer and Allen (1991). The specific objectives were achieved and the work also tried to work in a theoretical way for future work in this area in the UFC, although it is clear that no definitive research, it is very important that further research be undertaken, seeking to find new contributions of organizational commitment to the management of UFC. The research presented here covers a population of 52 subjects, with data collected by a duly completed and returned questionnaires. To collect the data, we adopted the questionnaire with closed Likert-type questions and an open, relating to classification level. The quantitative data analysis sought to compare the outcomes of organizational commitment in its three dimensions, according to the demographic / occupational information from participants. From the results, it was possible to identify the CT UFC a significant degree of organizational commitment within the three approaches, and the normative approach was one that had the highest average among the participants, showing that for most of these servers exist the sense of obligation to meet the standards and duties, to internalize the goals and values ​​of the organization.